Resolving inherited and de novo germline predisposing sequence variants by means of whole exome trio analyses in childhood hematological malignancies - Brozou, Triantafyllia; Yasin, Layal; Brandes, Danielle; Picard, Daniel; Walter, Carolin; Varghese, Julian; Dugas, Martin; Fischer, Ute; Borkhardt, Arndt; Haas, Oskar A. (Frontiers in Pediatrics, 2023)
Molecular screening tools have significantly eased the assessment of potential germline susceptibility factors that may underlie the development of pediatric malignancies. Most of the hitherto published studies utilize the comparative analyses of the respective patients’ germline and tumor tissues for this purpose. Since this approach is not able to discriminate between de novo and inherited sequence variants, we performed whole exome trio analyses in a consecutive series of 131 children with various forms of hematologic malignancies and their parents. In total, we identified 458 de novo variants with a range from zero to 28 (median value=3) per patient, although most of them (58%) had only up to three per exome. Overall, we identified bona fide cancer predisposing alterations in five of the investigated 131 (3.8%) patients. Three of them had de novo pathogenic lesions in the SOS1, PTPN11 and TP53 genes and two of them parentally inherited ones in the STK11 and PMS2 genes that are specific for a Peutz-Jeghers and a constitutional mismatch repair deficiency (CMMRD) syndrome, respectively. Notwithstanding that we did not identify a disease-specific alteration in the two cases with the highest number of de novo variants, one of them developed two almost synchronous malignancies: a myelodysplastic syndrome and successively within two months a cerebral astrocytoma. Moreover, we also found that the rate of de novo sequence variants in the offspring increased especially with the age of the father, but less so with that of the mother. We therefore conclude that trio analyses deliver an immediate overview about the inheritance pattern of the entire spectrum of sequence variants, which not only helps to securely identify the de novo or inherited nature of genuinely disease-related lesions, but also of all other less obvious variants that in one or the other way may eventually advance our understanding of the disease process.